Synthesis And Characterization Of Nanostructured Zinc Oxide (Zno) For Sensor Applications - Abdulgafour, Hind I. (2013)
This project focuses on the development of new approach to grow a variety of high quality ZnO nanostructures without catalyst through a low cost method by wet thermal evaporation for sensor applications. The growth of ZnO nano- and microstructures is by wet oxidation of Zn powder via the vapour–solid (VS) mechanism. In the first part of this work, the effect of different temperatures on synthesizing high quality ZnO nanostructures on Si/SiO2 substrate was studied. The growth temperatures could be divided into three regions: low (550-650˚C), moderate (700-800˚C), and high (850-900˚C), respectively. The fabrication of high quality ZnO nanostructures for sensor applications was confined in the moderate to high temperature regions. The influence of different durations on the growth of ZnO nanorods was also discussed. Apart from that, a novel fabrication of 3D ZnO microstructures and nanostructures at different temperatures in one step without catalyst was presented. The structural and optical properties as well as the growth mechanisms of various ZnO nanostructures have been investigated and proposed. The best performance device for ZnO tetrapod-like nanorods grown on Si/SiO2 was fabricated to study the effect of thermal annealing temperatures on the electrical properties of Pd/ZnO tetrapod-like nanorods. The enhancement of the photoresponse time of low cost Pd/ZnO tetrapod-like nanorods for ultraviolet (UV) detection was obtained. It was found that the maximum responsivity of the Pd/ZnO metalsemiconductor- metal (MSM) photodetector was 0.106 A/W at 300 nm which corresponds to a quantum efficiency of 43.8% at 5 V applied bias voltage.